A new species of Aegidium Arrow (Coleoptera: Scarabaeidae) from the Atlantic forest ecoregion in South America - Frolov, Andrey V.; Grossi, Paschoal C.; Vaz-De-Mello, Fernando Z. (Zootaxa, 2015)
The New World genus Aegidium Arrow (Coleoptera: Scarabaeidae: Orphninae) comprises mid-sized to rather large beetles belonging to 12 species (Paulian 1984). The species of this genus were known from the northern Amazon Basin and the Caribbean including some of the Lesser Antilles islands. Distribution records suggest that the primary habitat of Aegidium are Neotropical rain forests. The genus is distributed up to southern Mexico in the north (Morón 1991) and A. cribratum chileanum Paulian was described from Chile (Paulian 1984), but Aegidium has not been recorded southeast of the Amazonia. An interesting discovery was made by one of us (P.C.G.) who collected one male Aegidium specimen in the Atlantic forest patch near Nova Friburgo (Rio de Janeiro State, Brazil)—the area separated from the yet known range of the genus by vast territories occupied by the Cerrado biome. Examination of this specimen showed that it belongs to an undescribed species and differs sharply from the other congeners in the shape of its aedeagus. This new species is described and illustrated below.